Hybridization of hexagonal boron nitride nanosheets and multilayer graphene: Enhanced thermal properties of epoxy composites. (28th July 2020) - Akhtar, M. Wasim; Kim, Jong Seok; Memon, Muddassir Ali; Baloch, Muhammad Moazam
Abstract: We report an effective and reproducible method for hybridization of surface modified hexagonal boron nitride (h-BNNS) and multilayer graphene (MLG) by silane coupling agents. Simultaneously, silver (Ag) nanoparticles were grown on the interface of hybrid filler as a bridging agent during the hybridization process that activates free transportation of phonons when incorporated with epoxy matrix. Hybridization of surface modified h-BNNS and MLG improved the interfacial properties and the dispersion of the filler in the epoxy matrix. The hybrid filler BNNS-Ag-MLG (H-BSG) incorporated in the epoxy matrix and characterized for thermal properties. The thermal analysis confirmed that exceptionally improved thermal conductive and excellent thermally stable epoxy composite was fabricated. It was found that ~26 folds improvement in in-plane thermal conductivity was recorded by addition of 10 wt % of H-BSG in comparison with neat epoxy. This study indicates a step towards developing a strong interfacial connection between MLG and h-BNNS to make effective hybrid filler and emerging candidate for thermal interface applications.